Dead Zone Compensation and Adaptive Vibration Control of Uncertain Spatial Flexible Riser Systems - Zhao, Zhijia; Ahn, Choon Ki; Li, Han-Xiong (IEEE/ASME transactions on mechatronics, 2020)
This article provides a framework of dead zone compensation and robust adaptive vibration control for uncertain spatial flexible riser systems. First, nonsymmetric dead zone nonlinearity is represented in the form of the desired control input with the addition of an extra nonlinear input error. Second, by visualizing those input errors and extrinsic disturbances as an unknown "disturbance-like" term, a new robust adaptive vibration control technology and online updating laws can be constructed for riser systems to guarantee the oscillation reduction and compensation of uncertainties and dead zone. Third, the constructed control ensures and achieves bounded Lyapunov stability in the controlled system. Ultimately, control performances are demonstrated with appropriate design parameters.